Studies on chemical bath deposited SnS2 films for Cd-free thin film solar cells. Issue 4 (March 2017) - Gedi, Sreedevi; Minnam Reddy, Vasudeva Reddy; Pejjai, Babu; Park, Chinho; Jeon, Chan-Wook; Kotte, Tulasi Ramakrishna Reddy
Abstract: Tin disulfide (SnS2 ) is a simple binary metal chalcogenide and it has been proposed as a promising buffer material for Cd-free thin film solar cells. The present work explores the deposition of SnS2 films by a facile chemical bath deposition at different deposition times in the range of 30–120 min. The effect of deposition time on the structural, optical and electrical properties was investigated. The as-grown SnS2 films showed a hexagonal crystal structure with a high intensity (001) peak at 15.03°. The films showed shuttle shaped grains that were uniformly distributed across the surface of the substrate. The films showed an optical energy band gap in the range of 2.95–2.80 eV. PL spectra showed a strong emission peak in the wavelength range, 410–460 nm with the variation of deposition time. The SnS2 films prepared at a deposition time of 90 min showed good crystallinity and morphology with low resistivity of 11.2 Ω-cm. A solar cell with device structure of Mo/SnS/SnS2 /i-ZnO/Al: ZnO/Ni/Ag was fabricated. The fabricated solar cell showed an efficiency of 0.91%, which validate the photovoltaic performance of SnS2 films.